Role of callose synthases in transfer cell wall development in tocopherol deficient Arabidopsis mutants - Maeda, Hiroshi; Song, Wan; Sage, Tammy L.; DellaPenna, Dean (Frontiers in Plant Science, 2014)
Tocopherols (vitamin E) are lipid-soluble antioxidants produced by all plants and algae, and many cyanobacteria, yet their functions in these photosynthetic organisms are still not fully understood. We have previously reported that the vitamin E deficient 2 (vte2) mutant of Arabidopsis thaliana is sensitive to low temperature (LT) due to impaired transfer cell wall (TCW) development and photoassimilate export, associated with massive callose deposition in transfer cells of the phloem. To further understand the role of tocopherols in LT induced TCW development we compared global transcript profiles of vte2 and wild type leaves during LT treatment. Tocopherol deficiency had no impact on global gene expression in permissive conditions, but affected expression of 77 genes after 48 hours of LT treatment. In vte2 relative to wild type, genes related with solute transport were repressed, while those involved in various pathogen responses and cell wall modifications, such as GLUCAN SYNTHASE LIKE genes (GSL4 and GSL11), were induced. However, introduction of gsl4 or gsl11 mutations into the vte2 background did not suppress callose deposition or the overall LT-induced phenotypes of vte2. Intriguingly, introduction of a mutation of GSL5, the major GSL responsible for pathogen-induced callose deposition, into vte2 substantially reduced vascular callose deposition at LT, but again had no effect on the photoassimilate export phenotype of LT-treated vte2. These results suggest that GSL5 plays a major role in TCW callose deposition in LT-treated vte2 but that this GSL5-dependent callose deposition is not the primary cause of the impaired photoassimilate export phenotype.